Strategi Strategi Komunikasi Interpersonal Pengurus dalam Membentuk Karakter Disiplin Santri - Rofiah, Zaimatur Rofiah (ALAMTARA, 2024)
Interpersonal communication is communication that occurs between two or more people, whether within oneself or through direct or face-to-face interaction, so that messages can be conveyed and decisions can be reached. In this study, the intended interpersonal communication refers to the communication between the management in shaping the disciplinary character of the students. The purpose of this research is to determine the interpersonal communication strategies used by the management to develop the disciplinary character of students at Pondok Pesantren Tarbiyatut Tholabah Kranji Paciran Lamongan. The research questions in this study are: what are the interpersonal communication strategies of the management in shaping students' disciplinary character, and what are the supporting and inhibiting factors for the management in the process of developing students' disciplinary character. This study employs a qualitative and descriptive research method. Data collection techniques include field observations, interviews, and documentation. The theory used in this research is Miller and Steinberg's theory of interpersonal communication strategies, which includes the "dangling carrot" strategy (using praise as motivation), the "hanging sword" (as punishment for violators), and the catalyst strategy (to provide advice). The results of this study show that the management uses the "dangling carrot" strategy by giving praise or rewards, the "hanging sword" strategy as a sanction for rule violators, and the catalyst strategy to give advice to students. Supporting factors include cooperation between the community and the educational environment, while inhibiting factors include occasional management neglect of responsibility and a lack of individual awareness among students.